STRATEGI PENDIDIKAN INKLUSI TERHADAP PERKEMBANGAN AKADEMIK ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR - Kurniawan, Bayu; Laikha Listiyani; Siti Fatimah; Minsih; Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The increasing number of ABK cases in Indonesia has become a concern for the government and society. This leads to the necessity of holding inclusive schools in all schools. This research aims to analyze the impact of inclusive education on the academic achievement of children with special needs and appropriate strategies that influence the effectiveness of inclusive education in supporting the development of children with special needs. The method used is Systematic Literature Review. The articles used as data are articles published in 2022-2024. The results of this research are that inclusive schools have an important role in improving the learning achievement of ABK in elementary schools. The strategies used are: (1) the need for class teachers or subject teachers to master the ability to handle the problems of students with special needs; (2) the need for a GPK that is in accordance with the ABK ratio in the school; (3) initial assessment or initial identification of the student's special needs so that they receive appropriate treatment in the learning process; (4) Curriculum modifications are adjusted to suit the ABK in the class being taught; (5) evaluation of work programs that have been implemented; (6) Facilities and infrastructure that support children with special needs; (7) the active role of all parties, including the school, related stakeholders, and parents in creating an atmosphere of inclusion in learning.